Design study of outboard wing incorporating MFC for a morphing vehicle. (May 2023) - Mennu, Matlock; Tran, Brandon; O'Donnell, Richard; Tripp, Chad; Ifju, Peter
A novel biomimetic morphing micro aerial vehicle was designed using macro fiber composites (MFCs) as control actuators. The vehicle features variable-sweep, multi-curved wings, and a tail, both of which were embedded with MFC bimorphs. The wing design has a span of 1.1 m unswept (wings fully extended) and 0.65 m swept, resembling falcons (Falco Peregrinus). A design study was conducted on the outboard wing's MFC and carbon fiber substrate orientation to enhance the roll authority of the wings when fully extended. Finite element modeling, wind tunnel testing, and flight testing were conducted to model and optimize the design to obtain linear aerodynamic control with given MFC deflections. In addition, this research explores several configurations to increase roll authority of MFCs using segmented and overlapped sections resembling avian feathers. An overlapped wing configuration was discovered to have the potential to increase roll authority at the expense of adverse yaw. Flight testing proved that MFC-actuated, continuous outboard wings provide sufficient roll authority and handling quality without added compensation for the non-linear behavior of MFCs. This research showed that MFCs can be incorporated into a morphing wing design for manual flight and autonomous flight through feedback from inertial sensors onboard the vehicle.